Como resolver a equação 3x²-x-2? (Com a conta, por favor).
Soluções para a tarefa
Respondido por
8
Explicação passo-a-passo:
3x² - x - 2 = 0 (a = 3 ; b = -1 ; c = -2)
usando a fórmula quadrática, fica
x = -b ± √(b² - 4ac)
2a
x = - (-1) ± √((-1)² - 4 × 3 × (-2))
2 × 3
x = 1 ± √(1 + 24)
6
x = 1 ± √25
6
x = 1 ± 5
6
x₁ = 1 + 5 → x₁ = 6 → x₁ = 1
6 6
x₂ = 1 - 5 → x₂ = -4 → x₂ = -2
6 6 3
Perguntas interessantes
Sociologia,
10 meses atrás
Matemática,
10 meses atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Química,
1 ano atrás
ENEM,
1 ano atrás